ASSESSMENT OF MOTOR AND BATTERY SELECTIONS FOR ELECTRIC VEHICLE DEVELOPMENT - Chen, Lei; Panthong, Sorawit (Ayden International Journal of Basic and Applied Sciences, 2024)
Efficient electric vehicle design hinges on the precise calculation and selection of driving motors and power batteries. This study delves into the meticulous analysis of these crucial components, utilizing the fundamental parameters of electric vehicles presented in Table 1 as a reference point. By considering the specific requirements and characteristics of the electric vehicle, this research offers insights into the methodical process of determining the optimal driving motor and power battery, ensuring that the vehicle's performance and energy storage capacity align harmoniously with its intended application.